2017
DOI: 10.1016/j.chemphyslip.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Probing topology and dynamics of the second transmembrane domain (M2δ) of the acetyl choline receptor using magnetically aligned lipid bilayers (bicelles) and EPR spectroscopy

Abstract: Characterizing membrane protein structure and dynamics in the lipid bilayer membrane is very important but experimentally challenging. EPR spectroscopy offers a unique set of techniques to investigate a membrane protein structure, dynamics, topology, and distance constraints in lipid bilayers. Previously our lab demonstrated the use of magnetically aligned phospholipid bilayers (bicelles) for probing topology and dynamics of the membrane peptide M2δ of the acetyl choline receptor (AchR) as a proof of concept. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…(D) Membrane depth parameter (φ) as a function of Q1VSD residue position in POPC/POPG lipid-bilayered vesicles at 295 K. (Adapted from [84] with permission). SDSL CW-EPR spectroscopy at the X-band can also be used to study membrane topology of membrane proteins/peptides bound to aligned phospholipid bilayers [86][87][88][89][90].…”
Section: Figure 5 (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…(D) Membrane depth parameter (φ) as a function of Q1VSD residue position in POPC/POPG lipid-bilayered vesicles at 295 K. (Adapted from [84] with permission). SDSL CW-EPR spectroscopy at the X-band can also be used to study membrane topology of membrane proteins/peptides bound to aligned phospholipid bilayers [86][87][88][89][90].…”
Section: Figure 5 (A)mentioning
confidence: 99%
“…Figure 6 shows the membrane depth parameter as a function of the active pinholin S 21 68 residue position in DMPC lipid-bilayered vesicles at room temperature and the proposed topology model of the S 21 68 in DMPC lipid bilayers [66]. SDSL CW-EPR spectroscopy at the X-band can also be used to study membrane topology of membrane proteins/peptides bound to aligned phospholipid bilayers [86][87][88][89][90].…”
Section: Figure 5 (A)mentioning
confidence: 99%
“…Studies using EPR spectroscopy, pulse, and CW with spin labeling have also used bicelles as a lipid mimetic to study the conformational dynamics of IMPs. Magnetically aligned bicelles were used to probe the topology and orientation of the second transmembrane domain (M2δ) of the acetylcholine receptor using spin labeling and CW EPR [ 174 ]. Further, the immersion depth of the spin-labeled M2δ peptide at different positions in bicelles was determined.…”
Section: An Overview Of the Most Widely Used Lipid Membrane Mimetics And Their Applications In Functional And Structural Studies Of Integmentioning
confidence: 99%
“…The result of this study suggested that the EPR spectra of a bifunctional spin label can be used to accurately determine the orientation and rotational dynamics of an α -helical segment of an integral membrane protein in magnetically aligned bicelles. Recently, the Lorigan lab determined accurate helical tilt angle and dynamics of the AchR M2 δ peptide by utilizing the magnetically aligned bicelles EPR technique and multiple TOAC labeled peptide substitutions [ 71 ].…”
Section: Application Of Sdsl Epr Techniques For Studying Membrane mentioning
confidence: 99%